(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The dichotomy of “good” and “evil” is one of the most enduring and universal themes in human communication, often reflected in moral, religious, literary, and cultural discourse. This study focuses on the stylistic structures of English sentences that express these two opposing moral concepts. Drawing from a multidisciplinary perspective that includes stylistics, semantics, and discourse analysis, the paper investigates how language - through lexical choices, syntactic patterns, modality, and figurative expressions - serves to encode, reinforce, or challenge perceptions of moral goodness and wickedness. Particular attention is given to how adjectives, adverbs, metaphors, and symbolic language are used to intensify or soften moral judgment. The analysis covers a range of genres including religious texts, classical and modern literature, media discourse, and everyday conversation. It also highlights how sentence structure (such as passive voice, parallelism, and inversion) can subtly influence the emphasis or tone of moral evaluations.